Peran Artificial Intelligence terhadap Optimalisasi Pembelajaran Mahasiswa Universitas Brawijaya - Mumtaz, Tsabitah Zain; Isna, Fariha Nurul; Abadi, Machrus (Multiverse: Open Multidisciplinary Journal, 2023)
This research delves into the phenomenon of artificial intelligence in the realm of education, with a specific focus on its implementation in the learning system at Brawijaya University. The study aims to observe the practical application of artificial intelligence and analyze its role in enhancing the overall learning experience for students. Utilizing a qualitative research model, the researcher acts as the primary instrument, gathering data on students' interactions with artificial intelligence during the learning process and extracting relevant literature on the subject. The analysis involves three key stages: theme identification, data interpretation, and data presentation. The findings underscore the integral role of artificial intelligence as a learning medium at Brawijaya University, emphasizing its substantial contribution to optimizing the learning process.